Problem pokoju z Rosją bolszewicką w polskich analizach i opiniach w kontekście rokowań ryskich (wybrane przykłady) - Gmurczyk-Wrońska, Małgorzata (1963– ) (Instytut Historii PAN, 2024)
The article analyses documents presenting estimations and opinions on the possibility of concluding peace with Bolshevik Russia and the resulting threats and consequences for Poland and Europe. These are mainly archival materials produced by military experts, intelligence services, and diplomatic services on peace with Bolshevik Russia. The topics are primarily presented from the Polish perspective, but the French standpoint is also included, although to a lesser extent. The inclusion of France in the subject matter was mainly due to the anti-Bolshevik stance of that country’s authorities, the importance of France in the international system after the First World War, and the numerous references to France in the documents used in the article.
p. 99-114
Summary in English.
Keywords: peace negotiations; Poland; Bolshevik Russia; Riga; Second Department of the Supreme Command of the Polish Army; Second Department of the Polish General Staff of the Polish Army; Ministry of Foreign Affairs; Matuszewski, Ignacy (1891-1946); Knoll, Roman (1898-1946); Rozwadowski, Tadeusz Jordan (1866-1928)